The Representation of Identity Politic of Banyumas Culture As a Javanese Sub-Culture in Banyumas Style T-Shirt Design - Sulyana Dadan; Heru Nugroho; Christian Budiman (Pelopor Publikasi Akademika, 2023)
Banyumasan T-shirt is one of the creative industry products in Banyumas that has function as cultural display as well as expression of identity politics. This is because the various designs in Banyumasan T-shirts show various cultural identities of Banyumas that different from other cultures, especially with the Javanese culture that has been regarded as the core culture. Therefore, this study aims to find out how the identity politics of Banyumas society are represented in Banyumasan T-shirts. The research method used is qualitative research method with semiotic approach from Rolland Barthes. Research materials are in the form of the design of five brands Banyumasan T-shirts that circulate in the region Banyumas. From the research, it was found that Banyumasan T-shirt design represented Banyumas culture as a sub-culture that has different culture with Javanese culture. The visual and verbal texts display the Banyumas character of the cablaka (honest), egalitarian, critical and humorous. This is different from the construction of Javanese characters that tend to be closed, stratified, obedient and serious.